Human Papillomavirus Serology Among Women Living With HIV: Type-Specific Seroprevalence, Seroconversion, and Risk of Cervical Reinfection. (30th May 2018) - Kelly, Helen; Faust, Helena; Chikandiwa, Admire; Ngou, Jean; Weiss, Helen A; Segondy, Michel; Dillner, Joakim; Delany-Moretlwe, Sinead; Mayaud, Philippe
Abstract : Seroprevalence of type-specific HPV antibodies was high among women living with HIV in South Africa. The simultaneous seropositivity for all nonvalent vaccine types was observed in a minority of women. Seroconversion over 16 months was dependent on CD4+ cell count. Abstract: Background: Human papillomavirus (HPV) serodynamics following infection has never been evaluated prospectively among women living with HIV (WLHIV). We determined HPV seroprevalence, seroconversion, and cervical HPV-DNA acquisition among WLHIV. Methods: Prospective study of 604 WLHIV in Johannesburg, South Africa aged 25–50 years. At baseline and 16 months (endline), HPV type-specific antibodies (HPV6/11/16/18/31/33/35/39/45/52/56/58/59/68/73) were measured using HPV-pseudovirions and cervical HPV-DNA genotypes using INNO-LiPA. Results: Seroprevalence of any-HPV was 93.2% and simultaneous seropositivity for HPV types of the bivalent (HPV16/18), quadrivalent (HPV6/11/16/18), and nonavalent (HPV6/11/16/18/31/33/45/52/58) vaccines were 21.4%, 10.9%, and 2.8%. Among 219 women with cervical HPV-DNA, same-type seronegative and without high-grade cervical intraepithelial neoplasia at baseline, 51 (23.3%) had type-specific seroconversion at endline. Risk of type-specific seroconversion was higher among recent antiretroviral therapy users (ART ≤2 years vs ART naive: adjusted OR [aOR] = 2.39; 95% CI, 1.02–5.62), and lower among women with low CD4 + at endline (≤350 vs >350 cells/mm 3 : aOR = 0.51; 95% CI, 0.24–1.07). Risk of cervical HPV-DNA acquisition was lower in women seropositive for HPV18, 35, and 58 at baseline. Conclusion: WLHIV have evidence of seroconversion in response to baseline HPV-DNA, dependent on CD4 + count and ART. Baseline HPV seropositivity confers limited protection against some HPV types.